A case report of the rarest anal cancer: Basal cell carcinoma. (February 2022) - Tung, Jivatesh; Lin, Bruce; Schlenker, James; Simianu, Vlad V.
Abstract: A 69-year-old male truck driver with history of chronic anal fissures and facial basal cell carcinoma developed rectal bleeding and pain, and was diagnosed with a 5cm basal cell cancer of the anus with sphincter invasion. His workup entailed physical exam, CT and MRI which confirmed external and internal sphincter invasion without evidence of distant metastatic disease. After review of chemoradiation and surgical options, the patient elected to proceed with robotic-assisted abdominoperineal resection with end colostomy with complex local-tissue reconstruction. He is now two years out and disease free. While radiation and surgery have both been described in the literature as viable treatments, surgical resection may be the best option for patients with large lesions with sphincter invasion, who travel from afar and have occupational restrictions. This case highlights the importance of a multidisciplinary approach in assessing the patient with a rare disease process, presenting all viable options for treatment, and electing the optimal treatment through shared decision making. Highlights: Basal (BCC) cell carcinoma makes up less than 1% of anorectal neoplasms. Radiation, cryotherapy, Moh's surgery, local excision, and abdominoperineal resection can be used for anal BCC. Due to it's rarity, we recommend a multidisciplinary approach for this pathology. Details of a robotic abdominoperineal resection with complex perineal closure performed are discussed. The highlight of this report lies in honoring patient's wishes and what treatment best fits their lifestyle.